(untitled) (Annals of Medical Research, 2021)
Aim: In this study, It was ivestigated to see if there was a correlation between dipper and non-dipper hypertension conditions and the MHR in patients newly diagnosed with hypertension.Material and Methods: One hundred and thirty-nine newly diagnosed hypertension patients who admitted department of cardiology. Patients were divided into two groups; dipper group and non-dipper group and Monocyte/HDL-cholesterol Ratio, high sensitive-C reactive protein and dipper/non-dipper status were examined.Results: There were 61 patients (mean age 47±13 and 48% male) in the dipper group and 78 patients (mean age 52±12and 49% male) in the non-dipper group. Mean MHR was 0.01550±0.00447 in dipper group and 0.01810±0.00661 in non-dipper group. Mean MHR was significantly higher in non-dipper group (0.009). There was a significant and positive correlation between MHR and Hs-CRP (r=0.350; p0.001).Conclusion: When compared to the patients newly diagnosed with dipper hypertension, it has a high MHR level in the group of patients with non-dipper hypertension.